2018
DOI: 10.1038/s41598-018-32913-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and phylogenetics of whiteflies and their endosymbiont relationships after the Mediterranean species invasion in Brazil

Abstract: The Bemisia tabaci is a polyphagous insect and a successful vector of plant viruses. B. tabaci is a species complex and in Brazil native species from the New World (NW) group, as well as the invasive species, Middle East-Asia Minor 1 (MEAM1) and Mediterranean (MED) were reported. For better understanding the distribution of the different species four years after the Mediterranean species invasion in Brazil, whiteflies were collected from 237 locations throughout the country between the years of 2013 and 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 79 publications
3
72
0
Order By: Relevance
“…In Brazil, the frequencies of Hamiltonella and Rickettsia remained very similar in B. tabaci MEAM1 species from 2015 to 2017. However, the same study reported the increasing of infection of Hamiltonella, Rickettsia and Wolbachia in MED species individuals from 2015 to 2017 [32]. In laboratory conditions, Rickettsia is vertically transmitted by female whiteflies at high rates ranging from 98%-99% [31,33].…”
Section: Discussionmentioning
confidence: 92%
“…In Brazil, the frequencies of Hamiltonella and Rickettsia remained very similar in B. tabaci MEAM1 species from 2015 to 2017. However, the same study reported the increasing of infection of Hamiltonella, Rickettsia and Wolbachia in MED species individuals from 2015 to 2017 [32]. In laboratory conditions, Rickettsia is vertically transmitted by female whiteflies at high rates ranging from 98%-99% [31,33].…”
Section: Discussionmentioning
confidence: 92%
“…In Brazil, the variability in the secondary endosymbionts found in MED is quite large and may be explained by the recent and different introductions of this species into the country (Moraes et al, 2018). MED populations typically harbor Hamiltonella, Rickettsia, Wolbachia, Cardinium, and Arsenophonus (Gueguen et al, 2010;Czosnek and Ghanim, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although whitefly diversity in Brazil has been surveyed extensively in recent years (49)(50)(51)(52)(53)(54), no study has been carried out specifically to explore the composition of whitefly communities colonizing cassava. Those studies carried out in other crops demonstrated that B. tabaci MEAM1 is the predominant species across Brazil in crops such as common bean, cotton, pepper, tomato and soybean.…”
Section: Specific Associations Between Endemic Populations Of B Tabamentioning
confidence: 99%
“…Those studies carried out in other crops demonstrated that B. tabaci MEAM1 is the predominant species across Brazil in crops such as common bean, cotton, pepper, tomato and soybean. Furthermore, B. tabaci MED, which was recently introduced in Brazil, has quickly spread and currently is present in five states from the South and Southeast regions (52)(53)(54). A small number of whitefly samples from cassava were analyzed in those studies, with B. tuberculata and Tetraleurodes acaciae prevalent and detected exclusively in cassava (51,54).…”
Section: Specific Associations Between Endemic Populations Of B Tabamentioning
confidence: 99%